Electromagnetic Absorber-Embedded Ka-Band Double-Layer Tapered Slot Antenna for the Reduced Radar Cross Section at X-Band - Wonkyo Kim; Youngwan Kim; Hee-Duck Chae; Jihan Joo; Jun-Beom Kwon; Ick-Jae Yoon (Applied Sciences, 2025)
An electromagnetic (EM) absorber-embedded Ka-band double-layer tapered slot antenna (DLTSA) is proposed in this work. The EM absorber is placed on both sides of the tapered radiating slots as a means of achieving the reduced monostatic radar cross section (RCS) at the X-band. A conventional tapered slot antenna (TSA) with EM absorbers at the same position suffers from the distorted current distribution from the feedline to the radiating slots and causes a degraded radiation performance with a tilted beam. In contrast, the DLTSA with EM absorbers maintains the impedance and radiation characteristics of the antenna without the EM absorbers, while achieving the reduced monostatic RCS for the cross-polarized incident wave. The functionality of the reduced RCS is verified with the 4-by-4 DLTSA array design. The 4-by-4 array prototype with FGM-125 EM absorbers is matched at the Ka-band with a 14.7 dBi boresight gain at 35 GHz. The monostatic RCS is measured in an indoor environment, showing 6.5 dB monostatic RCS reduction at the X-band on average, verifying the computed expectations. This work validates the possible use of EM absorbers at the front side of a missile seeker composed of end-fire radiating elements.